The Malay version of dialysis specific nutrition literacy scale (DSNLS): translation and face validation - Sulaiman, Norhasmah; Mohd Shukri, Nor Azwani; Karami, Sarah Muneera; Mohd Abu Bakar, Wan Azdie; Mat Ya, Roselawati (UniKL Royal College of Medicine Perak (UniKL RCMP), 2024)
Background: Nutrition literacy is essential for understanding, assessing, and utilising nutritional information, particularly in end-stage renal disease (ESRD) patients, to improve their overall wellbeing. A suitable tool is necessary to assess their level of nutrition literacy. Unfortunately, there is a lack of a specific nutrition literacy scale in the Malay language for the hemodialysis patients’ population. Therefore, the aim of this study is to translate and validate the Dialysis-Specific Nutrition Literacy Scale (DSNLS) into Malay. Methods: The questionnaire was forward and backward translated by experts in dietetics and linguistics following established guidelines, resulting in a pre-harmonised Malay translation and two backward English translations. An expert committee reviewed and harmonised these translated questions. The questionnaire was then evaluated through a cognitive interview and face validity assessment among 15 hemodialysis patients. Results: During the expert committee assessment, several phrases underwent revisions to improve clarity and comprehension. Respondents preferred that certain terms be replaced during pre-testing with common phrases used in nutrition education. All questions achieved a face validity index value greater than the acceptable value, indicating good validity (≥0.87). Conclusion: The Malay version of the DSNLS underwent translation and face validation, and the findings demonstrate that it is clear and comprehensible for evaluating nutrition literacy among local hemodialysis patients.